El monstruo femenino y la violencia liberadora en A girl walks home alone at night de Ana Lily Amirpour=The female monster and the liberating violence in A girl walks home alone at night (2014), by Ana Lily Amirpour - Useros Rodríguez, Silvia (Estudios Humanísticos. Filología, 2021)
El objetivo de este texto es analizar el monstruo femenino en el film A Girl Walks Home Alone at Night (Una chica vuelve a casa sola de noche, 2014), de Ana Lily Amirpour, exponiendo el giro del arquetipo de la mujer vampiro, para tratar el tema de la violencia patriarcal y, mediante una serie de referencias críticas de la teoría del cine feminista, con figuras como Barbara Creed, Pilar Pedraza y Laura Mulvey, entre otras, entender las nuevas manifestaciones de lo femenino y lo monstruoso. The aim of this paper is to analyze the female monster in Ana Lily Amirpour’s film A Girl Walks Home Alone at Night (2014), exposing the reversal of the female vampire archetype to address the violence of patriarchy, and through a series of critical references from feminist cinema theory with figures such as Barbara Creed, Pilar Pedraza, and Laura Mulvey, among others, to understand the new trends of the feminine and monstrosity.